OPTIMIZING BRONCHIAL ASTHMA MANAGEMENT: A COMPREHENSIVE ANALYSIS OF INHALER DEVICE EFFICACY AND PATIENT ADHERENCE (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This prospective study evaluated therapeutic adherence and inhalation technique errors in 60 adult asthma patients using either metered-dose inhalers (MDIs) or dry-powder inhalers (DPIs) in real-world clinical practice. Adherence (MMAS-8), inhalation technique (direct observation), and asthma control (ACT) were assessed.DPI users demonstrated significantly higher adherence and fewer critical mechanical errors compared to MDI users, particularly those using MDIs without spacers. However, DPI effectiveness depended on adequate inspiratory flow. Proper technique and high adherence were strongly associated with better asthma control.The findings highlight the need for personalized inhaler selection, mandatory spacer use with MDIs, and routine technique verification to improve asthma outcomes.
Keywords: asthma, inhaler technique, medication adherence, metered-dose inhaler, dry-powder inhaler, spacer, asthma control, MMAS-8, ACT.